Correlating lockdowns, mortality rates and air pollution: a deep learning imbued study of COVID-19 - Tabassum, Tahia; Rahman, Saiham; Mahmood, Moosfiqur Hassan; Siam, Md. Fahim; Mumu, Sadia Anika (Brac University, 2021)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Computer Science and Engineering, 2021.